Accounting principles - Weygandt, Jerry J.; Kieso, Donald E.; Kimmel, Paul D. (John Wiley & Sons Singapore Pte.Ltd, 2014)
Accounting Principles 12th Edition by Weygandt, Kimmel, and Kieso provides students with a clear introduction to fundamental accounting concepts. The Twelfth Edition helps students get the most out of their accounting course by making practice simple. Both in the print text and online in WileyPLUS with ORION new opportunities for self-guided practice allow students to check their knowledge of accounting concepts, skills, and problem solving techniques and receive personalized feedback at the question, learning objective, and course level. Newly streamlined learning objectives help students use